Minimum Equitable Dominating Partition Energy of a Graph - Avula, Sashi Kanth Reddy; Reddy, P. Siva Kota; Prakasha, K. N. (Journal of Informatics and Mathematical Sciences, 2018)
The partition energy of a graph was introduced by Sampathkumar et al. [12]. Motivated by this, we introduce the concept of minimum equitable dominating partition energy of a graph, \(E^E_p (G)\) and compute the minimum equitable dominating partition energy \(E^E_p (G)\) of few families of graphs. Also, we establish the bounds for minimum equitable dominating partition energy.